2020
DOI: 10.1002/acr.24361
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Limited Health Literacy on Patient‐Reported Outcomes in Systemic Lupus Erythematosus

Abstract: Objective. Health disparities in patient-reported outcomes by income and education are well documented; however, the impact of health literacy on patient-reported outcomes has received less attention. We examined independent effects of income, education, and health literacy on patient-reported outcomes in systemic lupus erythematosus (SLE). Methods. Data from the California Lupus Epidemiology Study (n = 323 participants) were used. Health literacy was assessed with a validated 3-item measure (ability to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…Also, this is the first study which used the HLVa questionnaire to assess vaccine literacy functional and interactive-critical skills and its associated demographic factors in these patients. It is important to underline that previous studies conducted in patients with autoimmune diseases have used tools to assess general health literacy but not exactly to evaluate vaccine literacy (Katz et al, 2021;Maheswaranathan et al, 2020;Wu et al, 2020). Future researchers should consider using Online Photovoice (OPV) to further research this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Also, this is the first study which used the HLVa questionnaire to assess vaccine literacy functional and interactive-critical skills and its associated demographic factors in these patients. It is important to underline that previous studies conducted in patients with autoimmune diseases have used tools to assess general health literacy but not exactly to evaluate vaccine literacy (Katz et al, 2021;Maheswaranathan et al, 2020;Wu et al, 2020). Future researchers should consider using Online Photovoice (OPV) to further research this topic.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study found lupus patients with limited health literacy had worse patient-reported outcomes. 13 A study from 1997 explored the prevalence of low health literacy among a small cohort of 94 SLE patients and found about half (48%) had low health literacy. 14 Another study of 108 SLE patients found no association between health literacy with hydroxychloroquine non-adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research on rare multisystemic, autoimmune connective tissue disease such as systemic sclerosis (SSc) and systemic lupus erythematosus (SLE) has primarily focused on patient general health literacy and barriers to ICT use. 7 8 There is a paucity of evidence on eHealth literacy among rheumatologic providers. In regard to SSc/SLE eHealth support, web-based resources are often of low quality, have inadequate readability and limited functionality.…”
Section: Introductionmentioning
confidence: 99%